PREVENTION OF DISMENORRHEA - Jum Natosba (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Dismenorrhea is a medical condition characterized by severe uterine pain during menstruation that manifests as cyclical lower abdominal pain. Dismenorrhea is classified into primary dismenorrhea in the absence of pathology and secondary dismenorrhea in the event of an identifiable pathological condition. About 40-70% of women of childbearing age suffer from dismenorrhea accompanied by associated psychological, physical, behavioral, and social distress. This is the main cause of the decline in the quality of life of adolescents. The pathophysiological process due to increased myometrium activity caused by excessive production of prostaglandins that cause ischemia. Risk factors are very important in enforcing the diagnosis of dismenorrhea and also in distinguishing between primary and secondary dismenorrhea. Mainstay treatment is generally supportive by relieving symptoms in primary dismenorrhea and surgical treatment may be recommended for secondary dismenorrhea. Therefore, patients with primary dismenorrhea may only require simple non pharmacological and analgesic therapies, whereas patients with secondary menorrhea require treatment for major problems.